Mechanisms of PARP inhibitor sensitivity and resistance - D’Andrea, Alan D. (DNA repair, 2018)
BRCA1 and BRCA2 deficient tumor cells are sensitive to inhibitors of Poly ADP Ribose Polymerase (PARP1) through the mechanism of synthetic lethality. Several PARP inhibitors, which are oral drugs and generally well tolerated, have now received FDA approval for various ovarian cancer and breast cancer indications. Despite their use in the clinic, PARP inhibitor resistance is common and develops through multiple mechanisms. Broadly speaking, BRCA1/2-deficient tumor cells can become resistant to PARP inhibitors by restoring homologous recombination (HR) repair and/or by stabilizing their replication forks. Here, we review the mechanism of PARP inhibitor resistance.